The Effect Of Communication, Work Motivation, and Stress Work On The Performance Of Civil Servants At The Service Of Population and Civil Registration Bojonegoro District - Ninin Nike Pebriyati; Darianto Darianto; Muhammad David (International Journal of Economics, Business and Innovation Research, 2023)
This study aims to analyze the Effect of Communication, Work Motivation, and Work Stress on the Performance of Civil Servants at the Population and Civil Registration Office of Bojonegoro Regency. This type of research uses quantitative approach methods. The research sample of 59 respondents with the sampling technique in this study is the Non-Probability Sampling technique. The population in this study is all civil servants at the Population and Civil Registration Office of Bojonegoro Regency. Data collection instrument by distributing questionnaires. This research was conducted at the Population and Civil Registration Office of Bojonegoro Regency. This study used SPSS for Windows version 25. The results of this study show that the variables of communication, work motivation, and work stress on the performance of civil servants at the Population and Civil Registration Office of Bojonegoro Regency are all valid reliable, and normal statements. The results showed that the effect of communication, work motivation, and work stress had a partial and simultaneous effect on performance. Work motivation has